Response inhibition and reward anticipation in medication-naïve adults with attention-deficit/hyperactivity disorder: A within-subject case-control neuroimaging study - Carmona, Susana; Hoekzema, Elseline; Ramos-Quiroga, J. Antoni; Richarte, Vanesa; Canals, Clara; Bosch, Rosa; Rovira, Mariana; Carlos Soliva, Juan; Bulbena, Antonio; Tobeña, Adolf; Casas, Miguel; Vilarroya, Oscar (Human brain mapping, 2012)
Background: Previous research suggests that ADHD patients are characterized by both reduced activity in the inferior frontal gyrus (IFG) during response inhibition tasks (such as the Go‐NoGo task), and reduced activity in the ventral striatum during reward anticipation tasks (such as the Monetary‐Incentive‐Delay [MID] task). However, no prior research has applied either of these paradigms in medication‐naïve adults with ADHD, nor have these been implemented in an intrasubject manner. Methods: The sample consisted of 19 medication‐naïve adults with ADHD and 19 control subjects. Main group analyses were based on individually defined regions of interest: the IFG and the VStr for the Go‐NoGo and the MID task respectively. In addition, we analyzed the correlation between the two measures, as well as between these measures and the clinical symptoms of ADHD. Results: We observed reduced bilateral VStr activity in adults with ADHD during reward anticipation. No differences were detected in IFG activation on the Go‐NoGo paradigm. Correlation analyses suggest that the two tasks are independent at a neural level, but are related behaviorally in terms of the variability of the performance reaction time. Activity in the bilateral VStr but not in the IFG was associated negatively with symptoms of hyperactivity/impulsivity. Conclusions: Results underline the implication of the reward system in ADHD adult pathophysiology and suggest that frontal abnormalities during response inhibition performance may not be such a pivotal aspect of the phenotype in adulthood. In addition, our findings point toward response variability as a core feature of the disorder. Hum Brain Mapp 33:2350–2361, 2012. © 2011 Wiley Periodicals, Inc.